2020
DOI: 10.1097/phh.0000000000001230
|View full text |Cite
|
Sign up to set email alerts
|

Including Homeless Populations in Disaster Preparedness, Planning, and Response: A Toolkit for Practitioners

Abstract: Context: People experiencing homelessness are often the first and most severely affected group during disasters. Nonetheless, communities across the United States have frequently failed to adequately address the needs of homeless populations in disaster planning, response, and recovery. Communities must build multisector collaborative relationships and ensure that homeless service providers are adequately resourced. However, constraints in funding and staffing, combined with a lack of guidance about how to ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Prior research has identified lack of technology access or familiarity 6 - 8 and clients dropping out of care 8 , 9 as significant challenges for delivering appropriate care to Veterans in homeless programs through virtual telehealth modalities. Structural supports to facilitate their access, by referring patients to the Federal Communications Commission’s Affordable Connectivity Program, 38 the VA’s iPad program, which provides cellular-enabled tablets to patients to access tele-services, 39 and the VA’s Digital Divide Consult, which connects Veterans to a social worker to assist their enrollment in VA’s telehealth services programs, 40 may help address these barriers. Peer support, digital literacy, and motivational interviewing can also help some Veterans sustain their engagement with video-based care modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has identified lack of technology access or familiarity 6 - 8 and clients dropping out of care 8 , 9 as significant challenges for delivering appropriate care to Veterans in homeless programs through virtual telehealth modalities. Structural supports to facilitate their access, by referring patients to the Federal Communications Commission’s Affordable Connectivity Program, 38 the VA’s iPad program, which provides cellular-enabled tablets to patients to access tele-services, 39 and the VA’s Digital Divide Consult, which connects Veterans to a social worker to assist their enrollment in VA’s telehealth services programs, 40 may help address these barriers. Peer support, digital literacy, and motivational interviewing can also help some Veterans sustain their engagement with video-based care modalities.…”
Section: Discussionmentioning
confidence: 99%
“…People experiencing homelessness face a lack of regular shelter, as well as access to information and resources to prepare for and respond to wildfires, which amplify their wildfire smoke and health risk (Every et al 2014;Gin et al 2021;Gin et al 2022). Additionally, many people experiencing homelessness are also working in low-wage, frontline jobs and thus represent a portion of the labor force especially vulnerable to disruptions from smoke exposures.…”
Section: Housing-vulnerable People and People Experiencing Homelessnessmentioning
confidence: 99%
“…As a result, the only way to deal with this phenomenon is to be prepared, which can then prevent or reduce the amount of damage caused by it [ 7 , 8 ]. The health systems, as one of the main pillars of the communities, play the most important role in disaster risk reduction [ 4 , 9 ]. Disaster preparedness provides a platform for designing effective, realistic, and coordinated planning, reducing duplication of efforts and increasing its overall effectiveness and response efforts by National Societies, households, and community members [ 2 , 10 ].…”
Section: Introductionmentioning
confidence: 99%